ADDRESSING DIVERSITY IN SCIENCE EDUCATION: TEACHERS' CHALLENGES AND INNOVATIVE SOLUTIONS FOR INCLUSIVE EDUCATION - Zaman, Auliau Rachman; Vionita, Bunga Septria (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Inclusive science education requires an approach that is sensitive to student diversity, including differences in gender, culture, social background and learning ability. This process not only reflects social justice values, but also enriches students' learning experiences and prepares them to participate in an increasingly globalized society. However, many challenges are faced by science educators in their efforts to address this diversity in an effective way. This study explores the various challenges faced by teachers in dealing with diversity in the context of science education. Factors such as gender stereotyping, imbalance of cultural representation in teaching materials and inequality of access were highlighted. Teachers also face barriers in establishing a supportive and inclusive classroom environment for all students. Through a literature review and field research, this study explores innovative solutions adopted by science teachers to address these challenges. These initiatives involve inclusive curriculum design, the use of diverse role models, and the integration of technology to improve access and learning. In addition, teacher training focusing on cultural expertise and awareness of unconscious bias were also identified as key factors in creating inclusive learning environments. This research provides an in-depth insight into how science educators can face and overcome the challenges of diversity in the context of science education. Practical implications and policy recommendations will be outlined to support a more inclusive and relevant science education for all students in this global era.